2020
DOI: 10.5694/mja2.50781
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota‐derived trimethylamine N ‐oxide is associated with poor prognosis in patients with heart failure

Abstract: Objective: Gut microbiota-produced trimethylamine Noxide (TMAO) is a risk factor for cardiovascular events. However, conflicting findings regarding the link between plasma TMAO level and prognosis for patients with heart failure have been reported. We examined the association of plasma TMAO concentration with risk of major adverse cardiac events (MACEs) and all-cause mortality in patients with heart failure. Study design: Meta-analysis of prospective clinical studies. Data sources: We searched electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…Epidemiological studies have shown that heart failure (HF) is a growing global public health burden, with prevalence up to 1 to 2% in the adult population (1). Detection of novel biomarkers and mechanisms would be of significant clinical importance for the prevention and treatment of HF (2,3). It had been documented that metabolic disorders, including obesity, insulin resistance, and diabetes mellitus (DM) play an important role in the development and progression of HF (4).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that heart failure (HF) is a growing global public health burden, with prevalence up to 1 to 2% in the adult population (1). Detection of novel biomarkers and mechanisms would be of significant clinical importance for the prevention and treatment of HF (2,3). It had been documented that metabolic disorders, including obesity, insulin resistance, and diabetes mellitus (DM) play an important role in the development and progression of HF (4).…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure (HF) is a growing global public health burden, attributed to significantly increased mortality worldwide ( 3 ). Detection for the pathophysiological characteristics and novel treatment targets would be important for management of HF ( 4 6 ). It is well-documented that MS is an independent risk factor in the development of HF ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…To enable a consistent approach to the meta-analysis, we calculated the HRs per 1 SD increment in the level of HGI. If the included studies did not report effect measures as per 1 SD change, we converted the results according to the previously reported methods (26,27).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%